2018
DOI: 10.7554/elife.37122
|View full text |Cite|
|
Sign up to set email alerts
|

BRET-based RAS biosensors that show a novel small molecule is an inhibitor of RAS-effector protein-protein interactions

Abstract: The RAS family of proteins is amongst the most highly mutated in human cancers and has so far eluded drug therapy. Currently, much effort is being made to discover mutant RAS inhibitors and in vitro screening for RAS-binding drugs must be followed by cell-based assays. Here, we have developed a robust set of bioluminescence resonance energy transfer (BRET)-based RAS biosensors that enable monitoring of RAS-effector interaction inhibition in living cells. These include KRAS, HRAS and NRAS and a variety of diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 74 publications
1
51
0
Order By: Relevance
“…If the RLuc8 donor fusion molecule catalyzed the coelenterazine 400a and the GFP 2 acceptor fusion molecule is located less than 10 nm from the donor, a transfer of energy will occur from the donor to the acceptor. This method has been widely used to study PPI (Bery et al., ; Felce et al., ; Mercier et al., ) and also PPI inhibition by small molecules (Beautrait et al., ; Corbel et al., ; Corbel et al., ; Lavoie et al., ; Mazars & Fahraeus, ; Quevedo et al., ) or macromolecules (Bery et al., ; Guillard et al., ; Spencer‐Smith et al., ). It offers several advantages: it is a very sensitive technique as it is based on luminescence, there is no background signal from cellular autofluorescence.…”
Section: Commentarymentioning
confidence: 99%
See 2 more Smart Citations
“…If the RLuc8 donor fusion molecule catalyzed the coelenterazine 400a and the GFP 2 acceptor fusion molecule is located less than 10 nm from the donor, a transfer of energy will occur from the donor to the acceptor. This method has been widely used to study PPI (Bery et al., ; Felce et al., ; Mercier et al., ) and also PPI inhibition by small molecules (Beautrait et al., ; Corbel et al., ; Corbel et al., ; Lavoie et al., ; Mazars & Fahraeus, ; Quevedo et al., ) or macromolecules (Bery et al., ; Guillard et al., ; Spencer‐Smith et al., ). It offers several advantages: it is a very sensitive technique as it is based on luminescence, there is no background signal from cellular autofluorescence.…”
Section: Commentarymentioning
confidence: 99%
“…Accordingly, we have engineered genetically encoded Bioluminescence Resonance Energy Transfer 2 (BRET2)‐based RAS biosensors (Bery et al., ). These biosensors are optimized and comprised a full‐length RAS donor molecule (wild‐type and mutant K, N, and HRAS), to respect its intracellular localization, and several different known acceptor partners like PI3Kα, PI3Kγ and CRAF RAS binding domains (RBD) and the RAS associating (RA) domain of RALGDS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although to date some of these have been used to assist the identification of small molecules 5,7,21 , none has directly probed druggable pockets on RAS, as the majority of these biologics tend to bind over large protein interfaces 14,15,17,20 that are difficult to mimic with small molecules 22 . As some biologics form smaller interfaces 19,23,24 there emerges the tantalising prospect that biologics could be used as tools to identify druggable pockets and novel conformers, and could also have the potential to act as pharmacophore templates for in silico-informed drug discovery.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, recent studies have demonstrated that several molecules that bind to either RAS or effector proteins can inhibit RAS signaling by disrupting the interaction between RAS and effector proteins. These include peptides and proteins [3][4][5][6], antibody and antibody fragment [7,8], and small molecule compounds such as sulindac sulfide and its derivatives [9][10][11][12], MCP compounds [13,14], Kobe0065 and Kobe2602 [15], rigosertib [16], Abd series compounds [17], and compound 3344 [18]. Moreover, several independent groups developed small molecules that selectively inhibit oncogenic KRAS (G12C) mutant by covalently binding to Cys-12 to disrupt its effector interaction; these include acrylamide analogue 12 [19], GDP analogues (SML-8-73-1, SML-10-70-1) [20], ARS-853 [21,22] and ARS-1620 [23].…”
Section: Introductionmentioning
confidence: 99%